Results of analysis of temperature monitoring data around the nuclearly hazardous cluster of fuel-containing materials in the sub-reactor room 305/2 of the "Shelter" object, inside and outside the new safe confinement - O. V. Mykhailov; A. O. Doroshenko; M. V. Saveliev (Âderna Fìzika ta Energetika)
The results of the analysis of temperature monitoring data were obtained using the information and measuring system (IMS) "Finish" (1991 - 2015) and expert research system, new safe confinement (NSC) integrated control system in the main volume (MV) under the arched space, and the weather station in Chornobyl (1991 - 2023). After the NSC was installed in the design position, a slight increase in average annual MV NSC air temperature was observed before 2021. During the same period, the average annual temperature of concrete around the localization area of nuclearly hazardous clusters of fuel-containing materials (FCM NHC) in room 305/2 of the "Shelter" object increased by 1.3 - 1.4 times and had returned to 0.7 - 0.8 of the value of 1991. From 2021, no next increase in the mean annual temperature of concrete has been noticed. As of 2023, if compared to the monitoring period before Arch pushed into its design position, the calendar shift between the temperature of concrete and the surrounding environment enhanced to 1 month, according to both minimum and maximum average month values.